THE SYMBOLIC THOUGHT OF ASKA AND MAURA IN AURALASKA: A GEORGE HERBERT MEAD’S PERSPECTIVE - Banu Wicaksono Wicaksono; Anton Wahyudi (LPPM Universitas PGRI Jombang, 2025)
This study aims to examine the thoughts of the main characters through the perspective of George Herbert Mead's symbolic interactionism, specifically impulse, perception, manipulation, and consummation. This research employs a qualitative method. The data sources are sentences or dialogues of the main characters in the novel. The findings indicate that the characters' thoughts in the novel demonstrate symbolic thinking abilities in their interactions, particularly in the main characters, Maura and Aska. The symbolic thought interaction highlights the strength of consideration by taking into account the cause-and-effect relationships related to each character's actions. In the symbolic concept of mind, the results show that Maura is the most prominent character as the subject in the novel, while Aska functions as the object.